Towards Housing Policies: Urban Sprawl and Housing Disparities in Jakarta–West Java Growth Corridor - Putri, Kintansari Adhyna; Hidayat, Ikhtiar Anugrah; Triyogo, Muhammad Athallah Alif Bimo (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2025)
Rapid urbanization in metropolitan cities such as Jakarta has resulted in a growing disparity in house prices between the city center and suburban areas. This present study examines the economic determinants of housing unaffordability, with a focus on Gross Domestic Regional Product (GDRP) and Construction Expensiveness Index (CCI). This study employs a case study of the Jakarta and West Java regions to analyze the impact of these economic indicators on housing affordability and the extending gap between urban and peri-urban areas. The study indicates that higher construction costs in urban centers substantially worsen affordability challenges. Additionally, the study explores the question whether migration to suburban areas represents a significant trend and potential policy measure to address this disparity. The results of the study highlight the interconnectedness of economic growth, construction costs, and affordable housing availability in both urban and suburban contexts. To mitigate housing inequality and foster equitable regional development, this paper proposes policy interventions such as zoning reforms, enhanced public transportation infrastructure, and alternative housing models like Rent-to-Own (RTO).